2022
DOI: 10.1021/acsmeasuresciau.2c00055
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing 19F Benchtop NMR Spectroscopy by Combining para-Hydrogen Hyperpolarization and Multiplet Refocusing

Abstract: Benchtop NMR spectrometers provide a promising alternative to high-field NMR for applications that are limited by instrument size and/or cost. 19 F benchtop NMR is attractive due to the larger chemical shift range of 19 F relative to 1 H and the lack of background signal in most applications. However, practical applications of benchtop 19 F NMR are limited by its low sensitivity due to the relatively weak field strengths of benchtop NMR spectrometers. Here we present a sensitivity-enhancement strategy that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Collapsing NMR spectra into sharp singlets Using a benchtop NMR instrument, we have recently presented a SABRE-SHARPER experiment 10 , in which the SHARPER acquisition module provided a further boost (up to 17-fold) to a hyperpolarised signal by removing inhomogeneous broadening, refocusing homo-and heteronuclear J couplings and chemical shift differences on the order of 75 Hz. Using the pulse sequence of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Collapsing NMR spectra into sharp singlets Using a benchtop NMR instrument, we have recently presented a SABRE-SHARPER experiment 10 , in which the SHARPER acquisition module provided a further boost (up to 17-fold) to a hyperpolarised signal by removing inhomogeneous broadening, refocusing homo-and heteronuclear J couplings and chemical shift differences on the order of 75 Hz. Using the pulse sequence of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[84,85] However, structural perturbation may be especially notable for tags that contain higher numbers of fluorine atoms for sensitivity purposes, which will therefore, be larger, more lipophilic and more polarizing. Low signal-to-noise ratio can also be compensated by using advanced hardware such as cryoprobes or by developing new pulse sequences such as SHARPER, which collapses multiple fluorine signals into a singlet with greater signal-to-noise ratio, [86] albeit, this will be less useful for studying multiple species simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has been ongoing in low-field benchtop NMRs to improve their sensitivity for low-sensitive nuclides through hyperpolarization. [70][71][72][73][74] Poor resolution issues in low-field NMR can sometimes be ameliorated with chemometrics for structural analysis of molecules with low-to-medium complexity. Low-field benchtop NMR spectrometers have a great range of applications as online detectors of molecules with low-to-medium structural complexity, in sample or reaction mixtures.…”
Section: Basic Comparison Of Low-field Benchtop Nmrs With High-field ...mentioning
confidence: 99%
“…The study concluded that low‐field benchtop NMRs are not that useful for structure elucidation of complex unknown materials because of their low resolution compared with high‐field NMR spectrometers. In addition, research has been ongoing in low‐field benchtop NMRs to improve their sensitivity for low‐sensitive nuclides through hyperpolarization 70–74 . Poor resolution issues in low‐field NMR can sometimes be ameliorated with chemometrics for structural analysis of molecules with low‐to‐medium complexity.…”
Section: Basic Comparison Of Low‐field Benchtop Nmrs With High‐field ...mentioning
confidence: 99%